New fossils of Miotragocerus gluten from the Lower Siwaliks, Pakistan - Kiran Aftab; Muhammad Shadab; Muhammad AKbar Khan; Mubashar Hussain; Muhammad Adeeb Babar; Syed Ghyour Abbas; Muhammad Faheem Malik; Riffat Iqbal; Areej Arif (Kuwait Journal of Science)
The specimens of Miotragocerus gluten are collected from the Lower Siwalik outcrops nearby Chabbar Sayadan and Phadial. The newly discovered specimens include the two horn cores and isolated teeth. Miotragocerus gluten are the medium sized bovids, having brachydont to sub-hypsodont type of dentition. The cusps are elevated, and the crown is surrounded by a rugose enamel layer. The present study reveals the abundance of bovids in the middle Miocene deposits which indicates a grassland ecosystem in this area.